Red cell membrane disorders. (May 2017) - Narla, J.; Mohandas, N.
Abstract: Significant advances have been made in our understanding of the structural basis for altered cell function in various inherited red cell membrane disorders with reduced red cell survival and resulting hemolytic anemia. The current review summarizes these advances as they relate to defining the molecular and structural basis for disorders involving altered membrane structural organization (hereditary spherocytosis [HS] and hereditary elliptocytosis [HE]) and altered membrane transport function (hereditary overhydrated stomatocytosis and hereditary xerocytosis). Mutations in genes encoding membrane proteins that account for these distinct red cell phenotypes have been identified. These molecular insights have led to improved understanding of the structural basis for altered membrane function in these disorders. Weakening of vertical linkage between the lipid bilayer and spectrin‐based membrane skeleton leads to membrane loss in HS. In contrast, weakening of lateral linkages among different skeletal proteins leads to membrane fragmentation and decreased surface area in HE. The degrees of membrane loss and resultant increases in cell sphericity determine the severity of anemia in these two disorders. Splenectomy leads to amelioration of anemia by increasing the circulatory red cell life span of spherocytic red cells that are normally sequestered by the spleen. Disordered membrane cation permeability and resultant increase or decrease in red cell volume account for altered cellular deformability of hereditary overhydrated stomatocytosis and hereditary xerocytosis, respectively. Importantly, splenectomy is not beneficial in these two membrane transport disorders and in fact contraindicated due to severe postsplenectomy thrombotic complications.